The relationship between self-esteem, job-search intensity and career decision-making among graduating students. - Abdullah, Norida; Ninggal, Mohd. Tajudin (Penerbit Universiti, UTeM, 2010)
This study examined the relationship between self-esteem, job-search intensity and career decision-making among graduating students. Quantitative method used was correlation research. The instruments used were the Rosenberg Self-Esteem Scale, Job-Search Intensity Scale, and the Career Decision-Making Self-Efficacy Scale Short Form. A survey was conducted on 76 graduating students at Faculty of Information Technology and Communication, UTeM using cluster sampling procedure. The statistical tests used to analyze the data were Pearson correlation (r) at 0.01 sifnificant level, t-test and ANOVA at the 0.05 significant levels. The finding showed that there were a significant relationship between self-esteem and career decision-making self-efficacy, with job-search intensity and career decision-making self-efficacy. However, there was no significant relationship between job-search intensity and self-esteem. The results also showed that there were significant differences for self-esteem between students from different residential setting, and significant differences of self-esteem and job-search intensity based on ethinicity among the graduating students. The implications for students' development and career development centre were also discussed.